Filamentous fungi found in Atta sexdens rubropilosa colonies after treatment with different toxic bait formulations - Carlos, A. A. [UNESP]; Rodrigues, A. [UNESP]; Forti, L. C. [UNESP]; Passador, M. M.; Sierra, J. F. (Wiley-Blackwell, 2011)
Leaf-cutting ants maintain a symbiotic relationship with basidiomycetous fungi cultivated as food. Here, we profiled the non-symbiotic filamentous fungi in laboratory nests of Atta sexdens rubropilosa submitted to treatments with different toxic bait formulations (using the insecticide sulfluramide as the active ingredient). After treatment, several filamentous fungi were found in different nest compartments. Culture-dependent techniques recovered a total of 93 fungal isolates comprising 10 genera, 11 species and four unidentified fungi. The genus Penicillium was prevalent in both control and insecticide treatments. Overall, the majority of fungal isolates obtained in this study are commonly found in soil. Escovopsis spp., the specialized parasite of the ant-fungus mutualism was only recorded in the fungus gardens of nests submitted to the toxic treatments. Moreover, no correlation was found regarding the presence of fungi in the different nest compartments (chi-square, P > 0.4182). This study reveals that Escovopsis spp. is not the only fungus to overgrow the fungus garden of debilitated nests, thus adding more evidence on the possible negative impacts of such alien fungi. As suggested by previous studies, fast-growing filamentous fungi likely overgrow the fungus garden in such conditions.
Keywords: insecticide; leafcutter ants; microfungi; sulfluramide